Usmerjeno izobraževanje za opravljanje del in nalog na področju nege in zdravljenja v SR Sloveniji - Miloradović, Marija (Obzornik zdravstvene nege, 1981)
The paper deals with the system of directed education of the health staff in SR of Slovenia, which is to be introduced in 1981/82. The basic secondary education will offer three programmes, i. e. the programmes for health, laboratory and dental services. Duties of the nursing staff are defined separately. The paper describes the occupations ranging from the least to the largely complex ones, as well as the length of the education programme and professional qualifications for different jobs attainable at dillerent stages of the directed education. To implement the changes in the educational process, studies should be undertaken covering the work processes, progress in technology and organization of work. In keeping with the objective needs, individual interests and aspirations and the results of work, the workers will be directed to the in-service training and recurrent education programmes.